Indirect Routes to Aminoacyl-tRNA: The Diversity of Prokaryotic Cysteine Encoding Systems - Mukai, Takahito; Amikura, Kazuaki; Fu, Xian; Söll, Dieter; Crnković, Ana (Frontiers in Genetics, 2022)
Universally present aminoacyl-tRNA synthetases (aaRSs) stringently recognize their cognate tRNAs and acylate them with one of the proteinogenic amino acids. However, some organisms possess aaRSs that deviate from the accurate translation of the genetic code and exhibit relaxed specificity toward their tRNA and/or amino acid substrates. Typically, these aaRSs are part of an indirect pathway in which multiple enzymes participate in the formation of the correct aminoacyl-tRNA product. The indirect cysteine (Cys)-tRNA pathway, originally thought to be restricted to methanogenic archaea, uses the unique O-phosphoseryl-tRNA synthetase (SepRS), which acylates the non-proteinogenic amino acid O-phosphoserine (Sep) onto tRNACys. Together with Sep-tRNA:Cys-tRNA synthase (SepCysS) and the adapter protein SepCysE, SepRS forms a transsulfursome complex responsible for shuttling Sep-tRNACys to SepCysS for conversion of the tRNA-bound Sep to Cys. Here, we report a comprehensive bioinformatic analysis of the diversity of indirect Cys encoding systems. These systems are present in more diverse groups of bacteria and archaea than previously known. Given the occurrence and distribution of some genes consistently flanking SepRS, it is likely that this gene was part of an ancient operon that suffered a gradual loss of its original components. Newly identified bacterial SepRS sequences strengthen the suggestion that this lineage of enzymes may not rely on the m1G37 identity determinant in tRNA. Some bacterial SepRSs possess an N-terminal fusion resembling a threonyl-tRNA synthetase editing domain, which interestingly is frequently observed in the vicinity of archaeal SepCysS genes. We also found several highly degenerate SepRS genes that likely have altered amino acid specificity. Cross-analysis of selenocysteine (Sec)-utilizing traits confirmed the co-occurrence of SepCysE and the Sec-utilizing machinery in archaea, but also identified an unusual O-phosphoseryl-tRNASec kinase fusion with an archaeal Sec elongation factor in some lineages, where it may serve in place of SepCysE to prevent crosstalk between the two minor aminoacylation systems. These results shed new light on the variations in SepRS and SepCysS enzymes that may reflect adaptation to lifestyle and habitat, and provide new information on the evolution of the genetic code.